(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Abdurazak Gurnah’s The Last Gift deeply explores the relationship between memory, trauma and identity, weaving a narrative that examines the lasting effects of displacement and personal history. Through the protagonists fragmented recollections, the novel delves into the burden of migration, the struggle to create identity and the haunting presence of unresolved pasts. This paper analyses how Gurnah employs memory as both a narrative and a thematic device, illustrating the tension between personal and collective histories. By placing The Last Gift within the border of the Postcolonial Literature, this study highlights the novel’s engagement with the themes of exile, cultural hybridity, and the search for belonging. Ultimately, this paper argues that Gurnah’s portrayal of memory and trauma serves as a powerful lens through which identity is continuously negotiated and reconstructed.